(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the errors of class VII A students of SMP Negeri 2 Mandor in solving critical thinking problems on fractions using the Newman approach, considering that students’ critical thinking skills are still relatively low and affect the success of solving mathematical problems. The study used a qualitative descriptive method with a case study design. The research subjects were 26 students who were grouped into categories of high, medium, and low critical thinking skills. Data were collected through written tests and in-depth interviews. Data analysis was carried out through data reduction, data presentation, and drawing conclusions, and referring to Newman’s error analysis stages which include errors in reading, understanding problems, transformation, process skills, and writing final answers. The results showed that students made errors at all Newman stages, with the dominance of errors at the stages of understanding problems, transformation, process skills, and drawing conclusions. These errors were caused by weak conceptual understanding, low critical thinking skills, inappropriate learning strategies, as well as metacognitive factors and student anxiety when solving problems. The research findings indicate the need to strengthen learning oriented towards the development of critical thinking and problem-solving skills to minimize student errors in solving mathematical problems.